Movable Road Divider Using Internet of Things - Sushrutha, Anireddy; Reddy, C.R.K (International Journal of Computer Sciences and Engineering, 2020)
Road Divider is used for dividing the road for ongoing and incoming traffic. This helps keeping the flow of traffic in control. The problem with Static Road Dividers is that the number of lanes on either side of the road is fixed. This calls for better utilization of existing resources like number of lanes available.The main aim is to formulate a mechanism of automated road divider that can shift lanes at one side, so other side can have number of lanes in the direction of the rush. The cumulative impact of the time and fuel that can be saved by adding even one extra lane to the direction of the rush will be significant.With the smarter application proposed below,it will be helpful eliminate the dependency on manual intervention and manual traffic coordination to have a smarter traffic all over the city. An Automated road divider can provide a solution to the above mentioned problem effectively.